Investigating the Novel Hydrogen-Bonded Charge Transfer Complex between Chloranilic Acid and 2-Amino-4, 6-Dimethylpyridine: Spectroscopic Characterization, Molecular Modeling and DFT/TD-DFT/PCM Calculations - Al-Ahmary, Khairia M.; Alshehri , Fatimah A.; Atlam, Faten M.; Awad , Mohamed K. (Recent Developments in Chemistry and Biochemistry Research Vol. 1, 2024)
Spectroscopic analysis, molecular modelling, and DFT/TD-DFT/PCM calculations of a novel hydrogen-bonded charge transfer complex formed by chloranilic acid and 2-amino-4, 6-dimethylpyridine. A charge transfer hydrogen-bonded complex between the electron donor (proton acceptor) 2-amino-4,6-dimethylpyridine and the electron acceptor (proton donor) chloranilic acid was synthesised and explored experimentally and theoretically. The stability constant showed high values, indicating that the produced compound was highly stable. The stoichiometric ratio for chloroform, ethanol, methanol, and acetonitrile was found to be 1:1. The solid compound was created and characterised using various spectroscopic techniques. FTIR, 1H, and 13C NMR experiments confirmed the presence of proton and charge transfers in the produced complex. In addition to experimental data, molecular modelling using density functional theory (DFT) was performed in gas, chloroform, and methanol phases to account for charge and hydrogen transfers. Overall, experimental and theoretical computations were consistent.